Regulation of the Unfolded Protein Response in Disease: Cellular Stress and microRNAs - Lara-Reyna, Samuel; Scambler, Thomas; Holbrook, Jonathan; Jarosz-Griffiths, Heledd H.; Peckham, Daniel; McDermott, Michael F. (Current Immunology Reviews (Discontinued), 2018)
Background: The Unfolded Protein Response (UPR) is a well conserved mechanism that mammalian cells use to cope with stress and infections. This mechanism is exquisitely regulated at several levels, including post-transcriptional modifications by microRNAs. These small non-coding RNAs are mainly involved in the degradation of mRNA, thereby blocking protein translation. The finely balanced interplay between the UPR and microRNAs is altered in several disorders, contributing to both disease aetiology and pathology. Methods: We review and explore alterations in the UPR and microRNAs in several inflammatory conditions, including bone, lung, and neurodegenerative diseases. We also evaluate the impact of these alterations on the disruption of cellular homeostasis and suggest possible therapeutic options to restore this balance. Results: Several components of the UPR, including IRE1, ATF6, and PERK, are clearly dysregulated in inflammatory bone, lung, and neurodegenerative diseases, contributing to the inflammatory process in these disorders. XBP1s, which is downstream of IRE1, is shown to be dysregulated in several diseases, and significantly contributes to the inflammatory process. MicroRNAs show unique dysregulated signatures in each individual tissue and disorder, suggesting that these small transcripts may regulate different pathways in a cell-dependent manner. Finally, there are functional connections between these dysregulated microRNAs and the UPR, which may underlie important pathological aspects of these disorders. Conclusion: It is evident that microRNAs regulate several components of the UPR and that these small non-coding RNAs, or other molecules that restore the UPR balance, may represent possible therapeutic options to normalise intracellular homeostasis.
Keywords: PERK